Design and synthesis of quinoxaline derivatives for medicinal application against breast cancer cells - Lekgau, Karabo (My University, 2021)
Breast cancer is a malignant tumour that starts in the cells of the breast. Many studies revealed aromatase (CYP19A1) and cyclin-dependent kinase 2 (CDK2) as possible therapeutic targets regarding breast cancer treatment, because they play crucial roles in anti-apoptotic processes during cell proliferation. Quinoxaline derivatives have attracted a great deal of attention due to their biological activities against fungi, virus, bacteria and cancer. Computer modelling was employed in order to reduce time and cost by searching the library of molecules and identifying those which are likely to bind to the drug target. A library of new one hundred (100) nitro and amino quinoxaline alkyne derivatives were successfully designed and screened against target proteins (CYP19A1 and CDK2) using virtual screening technique and thirteen (13) molecules were identified to be hit compounds against both targets with the docking score ranging from -6.143 to -8.372 kcal/mol as a measure of binding affinity. The hit compounds were subjected to IFD in order to identify tight binding through intermolecular interactions with active site residues of the binding pocket of the target proteins. All identified nitro and amino quinoxaline alkyne derivatives were successfully synthesised in a multi-step reaction sequence and their spectroscopic analysis (NMR, FTIR and MS) were in good agreement with the proposed structures in a good to moderate yield. The newly synthesised novel amino and nitro-quinoxaline derivatives were evaluated for anti-proliferative activity against breast cancer (MCF-7). Compound 59 showed to possess good inhibition against MCF-7 with an IC50 of 9.102 μM, whereas compounds 34, 54, 56 and 61 showed promising activity against MCF-7 with an IC50 value of < 50 μM. However, the MTT assay results showed that 59 was found to be toxic with an IC50 value of 0.205 μM against Raw 264.7 cell line. The dose response investigations showed that 31 and 34 have the promising anti-cancer activity against CYP19A and the correlation between molecular modelling (in-silico) and CYP19A inhibition activities (in- vitro), was established as compounds 31 and 34 were identified to bind to the drug target (CYP19A) with the docking score of -8.372 and 7.630 kcal/mol respectively. All the synthesized compounds were evaluated for the antitubercular activity against Mtb H37Rv strain as a secondary study. Compounds 57-62 with nitro-quinoxaline derivatives exhibited stronger inhibitory effects on Mtb H37Rv strain. In addition, compounds 60 and 62 were found to be most active against Mtb H37Rv with the high activity at MIC90 of <0.65 and <0.64 μM respectively. All active compounds are currently investigated for their cytotoxicity which have not been investigated before.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2021
Keywords: Breast cancer; Quinoxaline alkyne; Cells; Molecules; Breast cancer; Body marking; Drug targeting; Breast cancer -- Treatment